Human Rights: International Protection, Monitoring,Enforcement - Symonids,Janusz.ed (Rwat publication;, 2005)
The series of volumes prepared by UNESCO for teaching human rights at higher education level comes to a successful conclusion with the publication of this volume. Human Rights: International Protection, Monitoring, Enforcement takes an institution Political Science, Social & Cultural Studies, Human Rights: International Protection, Monitoring, Enforcement~~ Janusz Symonides~~Political Science~~Social & Cultural Studies~~9781351218443, en, Human Rights: International Protection, Monitoring, Enforcement,